2017
DOI: 10.3389/fbioe.2017.00064
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Analysis of AP Foot Convexity: Insights into Smooth Muscle Biophysics

Abstract: Action potential (AP) profiles vary based on the cell type, with cells of the same type typically producing APs with similar shapes. But in certain syncytial tissues, such as the smooth muscle of the urinary bladder wall, even a single cell is known to exhibit APs with diverse profiles. The origin of this diversity is not currently understood, but is often attributed to factors such as syncytial interactions and the spatial distribution of parasympathetic nerve terminals. Thus, the profile of an action potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Also, only these cells, and to an extent their immediately neighboring cells, produced APs with convex AP feet. The majority of the cells in the syncytium exhibited a more “concave-upwards” rise to the AP peak, as has been reported previously (Appukuttan et al, 2017b ). This is seen for cell C in Figure 7 (green trace).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Also, only these cells, and to an extent their immediately neighboring cells, produced APs with convex AP feet. The majority of the cells in the syncytium exhibited a more “concave-upwards” rise to the AP peak, as has been reported previously (Appukuttan et al, 2017b ). This is seen for cell C in Figure 7 (green trace).…”
Section: Resultssupporting
confidence: 86%
“…In a previous study, we have demonstrated that an appropriate technique to measure the AP foot convexity involves evaluation of the area enclosed between a pre-defined line and the AP foot (Appukuttan et al, 2017b ). This technique is illustrated in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we have demonstrated that an appropriate technique to measure the AP foot convexity involves evaluation of the area enclosed between a pre-defined line and the AP foot (Appukuttan et al, 2017b). This technique is illustrated in Figure 3.…”
Section: Ap Features and Their Measurementsmentioning
confidence: 99%
“…The measure thus obtained is denoted as C X,Y indicating the measure of AP foot Convexity evaluated for a depolarization of Y mV over a time frame of X ms, where X and Y define the line. The values of X and Y for this study were selected in accordance with the requirements of this method (Appukuttan et al, 2017b). This approach has been shown to be more applicable over other methods such as evaluation of the radius of curvature along the AP curve.…”
Section: Ap Features and Their Measurementsmentioning
confidence: 99%